Are long hospitalizations substituting primary and long-term care? Evidence from Brazil and Mexico - Natalia Aranco; Sebastian Bauhoff; Natalie Schwarz; Marco Stampini (Inter-American Development Bank (IDB), 2024)
Prolonged hospital stays, or hospital stays that are longer than medically necessary, are a major concern for patients, payers, and providers. We conceptualize and empirically estimate the prevalence and cost of prolonged stays among elderly hospital patients (65 years and older) in Brazil and Mexico. We develop a continuum-of-care conceptual framework based on prior literature and insights obtained through interviews and focus group discussions with experts from Mexico, Argentina, and Colombia. In this framework, hospitals are part of a wider system. This system involves both pre-admission and post-discharge medical and social care services. There are three main sources of prolonged stays: (i) lack of appropriate primary healthcare that leads to more complex admissions; (ii) hospital inefficiency; and (iii) lack of rehabilitation, social, and long-term care at discharge. We estimate the count and share of inappropriate hospital days due to prolonged stays overall and for each source. This estimation is based on administrative records on discharges from public sector hospitals in 2019. Our results show that hospital days due to prolonged stays account for approximately half of all hospital days. Although most of the inappropriate days can be attributed to hospital inefficiency (36% in Brazil and 49% in Mexico), an important share is linked to the lack of rehabilitation, social, and long-term care. Lack of these services accounts for 12% of total hospital days in Brazil and 7% in Mexico. In a back-of-the-envelope calculation, we estimate that providing six weeks of long-term care services to address the care needs brought about by only thirteen causes of admission would generate annual net savings of approximately US174 million per year in Brazil and US45 million in Mexico.
Keywords: I10; J14; H5; J18; 330; healthcare costs; prolonged hospitalizations; primary health care; long-term care; medical care; population aging; older persons; public policy; social care; rehabilitation care; LatinAmerica and the Caribbean; Mexico; Brazil